IoT-Driven Kaizen for Enhanced Real-Time Warehouse Operations and Dynamic Inventory Visualization in FG Delivery - Mohd Rusli, Mohd Hazri; Mohamad Khairi Hassan; Ruben Balan Sigau; Muhamud-Kayat, Suzilawati; Mohd Yusof, Sha’ri (International Journal of Integrated Engineering, 2026)
Efficient inventory management within Finished Goods (FG) warehouses is a critical pillar of the Malaysian automotive manufacturing sector. Traditional manual recording methods often suffer from data latency and transcription inaccuracies, hindering real-time decision-making. This research implements an IoT-driven Kaizen system designed for real-time inventory control at a major automotive warehouse in Port Klang. By transitioning from manual whiteboard-based tracking to a digital framework—leveraging open-source tools such as AppSheet, Google Sheets, and Looker Studio—the system established a seamless, paperless data pipeline accessible via mobile and desktop devices. Results from the preliminary implementation demonstrate a 100% reduction in manual data entry lag and the total elimination of human transcription errors. Furthermore, the system optimized warehouse utilization, maintaining a 41.2% occupancy rate while successfully processing a throughput of 211,980 units. An interactive dashboard was developed to provide instantaneous stock visibility, significantly accelerating strategic interventions and mitigating the risk of inventory obsolescence. This digital transformation underscores the efficacy of low-cost IoT solutions in enhancing operational transparency and scalability within the industrial engineering landscape.